EKSTRAKSI BETASIANIN DARI KULIT UMBI BIT(Beta vulgaris) SEBAGAI PEWARNA ALAMI - Martinus Andree Wijaya Setiawan; Erik Kado Nugroho; Lydia Ninan Lestario (Agric, 2015)
The aim of this research was to know most effective solvent comparison (ethanol, ethanol:HCL, ethanol: Citric Acid) on the betacyanin extract properties from Beet Peel. The characteristic of Beet Peel contain 82,85 percent water, fiber 5,95 percent, ash 1,33 percent, and lipid 0,31 percent. The research was also aimed to know potential of Beet Peel for narutal dyes. This research was conducted only to compare effectivity of three different solvent that use to extract Beet Peel, temperature that use for extraction are the same at 30oC for 40 minute. The bestcharacteristic of extract was obtained from the ethanol:HCL with betalain of 2,4535 mg/100g.